Survei Motor Educability Mahasiswa Semester 1 Tahun Akademik 2023 Program Studi Penjaskesrek FKIP Unpatti - Manis Belen; Mariana D. Hukubun; Mieke Souisa (Departement of Mathematics Education, 2024)
The purpose of this study was to determine the motor educability of first semester students in the 2023 academic year, the penjaskesrek (PJKR) study programme. This type of research uses quantitative method analysis with survey techniques. Obtaining motor educability data through tests. The total population in the study was 46 students, determining the sample with porposive sampling technique obtained 30 female students. Sampling criteria by setting specific characteristics, namely age from 17-22 years. The test instrument used consists of 21 test items, namely: 1) On foot-touch head; 2) Sides lean rest; 3) Grapes vine; 4) One leg balance; 5) Stroke stand; 6) Double foot click; 7) cross-leg squats; 8) complete left turn; 9) one knee-Head to Floor; 11) Backward and forward hand kicks; 12) Arm circle in full squat; 13) Half-Tunnel Jump-Left Leg; 14) Three Dips; 15) Lateral Kick; 16) Kneel Leap to Feet 18) Full Left Turn; 19) The Top; 20) Single Knee Balancing; 21) Jump Foot. Data analysis techniques based on the number of percentage calculation intervals, by first scoring the raw data obtained based on five (5) categories, namely: Very High, High, Medium, Low, and Very Low. The results showed that the average mastery of motor educability in the Very High category was 19.04 per cent, the High category was 47.62 per cent, and the Low category was 33.34 per cent.